Effects of ischaemic post-conditioning on eccentric exercise-induced muscle damage - Chen, Si; Zhang, Chuan (Biology of Sport, 2024)
Exercise-induced muscle damage (EIMD) is a common phenomenon resulting from high intensity exercise that impairs subsequent performance. Ischaemic post-conditioning (IPOC) is a simple intervention that has been shown to reduce muscle damage after prolonged ischaemia, a condition mechanistically similar to EIMD. The purpose of this study was to determine whether IPOC could alleviate muscle damage after eccentric exercise. Thirty-two young male participants were randomized into either a sham ( n = 16) or an IPOC ( n = 16) intervention group. Biceps brachii muscle damage was induced by eccentric exercise, with IPOC or sham intervention applied on the dominant arm following exercise (3 cycles of 30 s ischaemia). Visual analogue scale (VAS) pain, arm circumference, muscle thickness, echo intensity, and microvascular function (using near-infrared spectroscopy) were measured bilaterally at baseline, 24, 48, and 72 hours after eccentric exercise. Biceps curl one repetition maximum (1RM) was also measured. 1RM was higher for the IPOC group at 48 and 72 hours (both p < 0.05). On the dominant arm, VAS pain was lower at 72 hours for the IPOC group ( p = 0.039). Muscle thickness was lower at all post-exercise time points for the IPOC group (all p < 0.05). VAS pain, echo-intensity, and arm circumference were elevated on the non-dominant arm in the sham group at 72 hours (all p < 0.05). These parameters all returned to the baseline level for the IPOC group at 72 hours (all p > 0.05IPOC could attenuate the decrease in strength, and alleviate EIMD with both local and remote effects after high-intensity exercise.